Reform der sozialen Sicherung: Kurzfassung - Friedrich Breyer; Wolfgang Franz; Stefan Homburg; Reinhold Schnabel; Eberhard Wille (Springer-Verlag; ZBW - Leibniz Information Centre for Economics, 2004)
The book analyzes the German welfare state. It starts from a theoretical perspective and then develops changes in social security, public health care, and unemployment insurance.
Additional information: Summary / Kurzfassung
Keywords: H55; J65; 330; Welfare state; social security; public health care; unemployment insurance; Welfare state; social security; public health care; unemployment insurance